Family Experience of Caring for a Diabetes Mellitus Patient: A Qualitative Study - Indah Wulandari; Kusnanto Kusnanto; Sony Wibisono; Titin Puspitasari (Jurnal Ners, 2020)
Introduction: Diabetes mellitus is a chronic disease that requires lifelong care. The treatment of diabetes mellitus patients at home requires a family role so then the patients can optimize their care. The diabetes complications can be reduced as a result. The aim of this study was to explore the family experience of treating diabetes mellitus patients at home.Methods: A semi-structured phenomenological approach including inductive thematic analysis was used in this research.  Thirteen family members of diabetes patients participated in the discussion. Participant recruitment was focused on families that have treated diabetes patients for more than 1 year with no complications. Data saturation occurred after 2-3 meetings per participant.Results: The experiences of the family members while caring for diabetes mellitus patient can be used to determine the presence of 5 themes: family feelings that appear when caring for diabetes mellitus patients, patient adherence to taking medication, patient’s disobedience of their diet, patient’s disobedience of activity and  the family expectations of the futureConclusion: In every theme, family experience obstacles arise between the families’ wants and the patients’ needs.  Diet and activity became a major obstacle to diabetic care at home. Some topics needed more attention, such as the information and support provided for the family.